VARIOUS ADVANTAGES IN EDUCATION - Nur Afifah, Rizqi; Simanullang, Tuti; Madhakomala, R (International Journal of Business, Law, and Education, 2022)
Education is the main factor for every country or nation to excel in global competition, it is also an investment in the future that will be profitable. Various improvements to the education system have been implemented and are close to achieving their goals. The quality education system is actually the spirit of the teachers as the executor of education. Teachers are the key to quality education and the most important factor in the teaching and learning process. This study provides an overview of various problems, advantages and disadvantages of education, differences and similarities between Indonesia's education system and foreign countries. Literature review is the method used in this research. The results of the study show that the advantages of education in Indonesia are (1) a diverse education system; (2) Transparent education system; (3) The curriculum is prepared directly by the experts. Weaknesses; (1) Educators who are not evenly distributed; (2) Educational facilities that are not evenly distributed; (3) The curriculum is still theoretical. Education in Indonesia places more emphasis on learning to read, write, and count for early childhood, learning time is very busy, always giving assignments at home. While abroad, early childhood education places more emphasis on playing and interacting to explore their environment, students only study in class about 30-40% and the rest is spent playing and interacting with their friends, not giving assignments or homework. The similarity is to focus on sharpening students' character intelligence, increasing students' practical abilities which will be needed in the future.